Loop - Enabling 3D stochastic geological modelling. Issue 1 (1st December 2019) - Ailleres, Laurent; Jessell, Mark; de Kemp, Eric; Caumon, Guillaume; Wellmann, Florian; Grose, Lachlan; Armit, Robin; Lindsay, Mark; Giraud, Jeremie; Brodaric, Boyan; Harrison, Matthew; Courrioux, Gabriel
Summary: Loop is a new open source 3D geological and geophysical modelling platform in full development. The new platform consists of 4 main work packages: Knowledge Management: use of AI techniques for knowledge extraction from literature, maps and reports using geological ontology. Geological rules will be encoded to ensure proper knowledge extraction. Geological Event Management: Loop is a time-aware geological modelling platform and the event manager is capturing topological and time relationship between geological objects and structural events Forward and inverse structural modelling: we will encode structural geological rules in a time-aware context to account for folds (including overprinting), faults, shear zones, unconformities and intrusions. The modelling is based on probabilistic modelling and allows for the definition of an objective function for geology and quantification of uncertainty via posterior probabilities. Uncertainty characterisation and modelling: using stochastic simulations or the result of Bayesian modelling, Loop allows for characterisation and quantification of 3D uncertainty.